Technical fitness changes of young rhythmic gymnasts during macro-cycle - Rutkauskaite, R.; Skarbalius, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Constantly growing complexity of performance programs in rhythmic gymnastic requires superior technical fitness level (Knoll et al., 2000). The technique of programs is exactly pre-established and limited. After the changes of competition rules now it is possible to register foreseeable actions and a coefficient of programs complexity (differences between designed and performed movements). No studies, which analyse rhythmic gymnastic technical fitness changes, are conducted. However observation and comparison of technical fitness can manage training process and foresee sports results. The aim of research was to analyse technical fitness changes of young 11-13 ear rhythmic gymnasts during year macro-cycle. Methods High peak performance rhythmic gymnasts (11-13 year, n=46) were observed. The material for this report has been collected on the basis of eight different training programs analysis. According to sport performance protocols and presentation assessment of technical fitness was registered designed and performed technical fitness coefficients. In order to assess experienced/non-experienced coaches and wish to take a risk by planing programs were used interview. Statistical analysis was done with one-way Analysis of Variances: ANOVA. Discussion/Conclusion No significant differences were defined between technical judgements on coefficients of all tools. The top ten gymnasts performed routines were more optimal with respect to other gymnasts: it was seen less differences between designed and performed actions and stable results all over the season. Significantly stable results all around the season demonstrated younger gymnasts. There was not found the best optimal training program among the rest, but it was determined that experienced coaches were planning programs more optimal. The results of interview is allowed to deny a presumption that coaches together with gymnasts were apt to take a risk by planning these programs. As follows from the literature and research results the main reasons which limiting declared technical fitness are: 1) the gymnasts functional fitness (Douda et al. 2000); 2) no rational placing of elements in the exercise composition; 3) the incomplete physical potential fitness is limiting realisation of motor potential fitness; 4) large variations of psychic state (incomplete self-confidence). Having in mind this alteration of technical fitness we raise the following questions: is it enough to compete with elite of gymnasts? And why did it happen at the age of 13-4 this alteration stops and at the same time the results of competition become worse?